2022
DOI: 10.3389/fbioe.2022.909727
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Fluorescent Sulfur Quantum Dots for Bioimaging and Biosensing

Abstract: The rapid industrialization has had a serious impact on the environment, leading to an increase in disease and healthcare problems. The development of simple and effective biosensors to achieve specific analyte detection and bioimaging can provide useful information for disease prevention and treatment. Sulfur quantum dots (SQDs), a new class of metal-free fluorescent nanomaterial, are being studied and applied in diagnostic fields such as bioimaging and biosensing due to their advantages of simple synthetic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…The synthesis of TiO 2 was carried out based on the method proposed by Aritonang et al [4], starting with the preparation of Ti(OH) 4 sol using solution B containing titanium tetraisopropoxide (TTIP) precursor in ethanol solvent. Acetylacetone was then added to the mixture [16], and it was refluxed at 55 o C, followed by calcination to form sol [17][18]. This process produced white TiO 2 crystals, as previously reported by Aritonang et al [19].…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…The synthesis of TiO 2 was carried out based on the method proposed by Aritonang et al [4], starting with the preparation of Ti(OH) 4 sol using solution B containing titanium tetraisopropoxide (TTIP) precursor in ethanol solvent. Acetylacetone was then added to the mixture [16], and it was refluxed at 55 o C, followed by calcination to form sol [17][18]. This process produced white TiO 2 crystals, as previously reported by Aritonang et al [19].…”
Section: Resultsmentioning
confidence: 61%
“…Based on observations of the luminescence properties of SCDs using UV light illumination (λ = 365 nm), a yellowishgreen color was produced during the process. The emergence of this color was due to competition between various emission centers (bright edge states) that dominate the optical properties of SCDs [18].…”
Section: Resultsmentioning
confidence: 99%
“…It has been well reported that the chemical structure of Sdots contains the polymeric sulfur core, that is, polysulfide ions ( S x 2– ). Recently, the polysulfide anion was employed as an excellent visible light photoredox catalyst for organic transformations. , The polysulfide anion induces the reactions via single-electron transfer-driven radical-mediated processes . Therefore, we anticipated that the generation of the ROS was one of the primary reasons for the inhibition of bacterial growth in the presence of sunlight.…”
Section: Resultsmentioning
confidence: 99%
“…The minimum inhibitory concentration (MIC) of Sdots was found to be 0.16 mg/mL (D1), 0.56 mg/mL (D2), and 1.13 mg/mL (D3). Generally, Sdots contain a relatively less amount of sulfur than a large amount of the surface-stabilizing agent poly­(ethylene glycol) (PEG). Therefore, the effective MIC concentration of Sdots based on the sulfur concentration is 0.01 mg/mL (D1), 0.034 mg/mL (D2), and 0.068 mg/mL (D3). , At the abovementioned MIC concentrations, a comparative study of bacterial growth observed after 6 h under sunlight, dark, and SBGC along with the control (C) is given in Figure (Figure S4, Supporting Information). In the plot, the significant inhibition of the growth in the presence of sunlight compared to SBGC is clearly observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation